Pengaruh Beban Kerja Mental Terhadap Kinerja Kurir Menggunakan Metode NASA-TLX - Riza Anta Maulana; Nurmalawati Nurmalawati; Muhammad Zeki; Yusnawati Yusnawati; Yusri Nadya; Dewiyana Dewiyana; Muzakir Muzakir (Universitas Teuku Umar, 2026)
PT. Global Jet Express (J&T Express) operates as a last-mile delivery logistics provider serving the delivery of documents and commercial packages in the Langsa City area, Aceh. Initial findings from in-depth interviews revealed that couriers frequently experience symptoms of mental fatigue, such as prolonged lethargy, mild dizziness, musculoskeletal pain, and a decrease in intrinsic motivation, particularly at the end of their shifts. This study aims to analyze the influence of mental workload on the operational performance of couriers, while simultaneously measuring workload levels using the NASA-TLX (National Aeronautics and Space Administration Task Load Index) instrument, which has been tested for validity and reliability in the context of cognitive-physical load assessment. Although subjective, this method allows for relative quantification and comparison between individuals across six dimensions of work pressure: Mental Demand, Physical Demand, Temporal Demand, Performance, Effort, and Frustration. Pearson correlation results showed a coefficient of r = -0.212 (p < 0.05), indicating a weak but statistically significant negative relationship between the average Weighted Workload (WWL) scores and delivery performance (number of packages per day). These findings reinforce the hypothesis that increased mental pressure contributes to a decline in operational efficiency, though it is not proportionally dominant. The distribution of NASA-TLX scores showed a dominance in the